IPM workshop in SE Asia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Southeast Asian Pesticide Management and IPM Workshop held in Pattaya Thailand during February 1987